Designing an effective, ambitious and coherent EU regulatory framework to tackle deforestation - Tropenbos International (2020)
This position paper outlines the views from Tropenbos International on a new European regulatory framework to address deforestation and forest degradation associated with EU consumption. We build on examples and reflections from producer countries where Tropenbos International works in, as well as recent information and reports. The paper specifically contributes to the public consultation from the European Commission (that runs from September – December 2020) on the impact assessment that investigates the suitability of a range of different demand-side measures to address deforestation and forest degradation associated with EU consumption. We see that for the EU to substantially reduce its contribution to global deforestation and play a leading role in achieving the Paris climate targets and the Sustainable Development Goals (SDGs), ambitious intervention measures are needed. These measures need to discourage unsustainable practices and encourage the fair and sustainable production, trade and consumption of commodities. This can be achieved only through an ambitious EU regulatory framework that has a smart mix of three components: (1) strong legislative demand-side measures; (2) additional supporting measures; and (3) partnerships with strong supply-side measures. This framework should be part of a wider set of measures to push for the required structural changes of international value chains in order to contribute to the SDGs and international climate goals and to reduce pressures on forest frontiers in the long term.